Attack-Resilient State Estimation for Uncertain Complex Networks with Fading Measurements and Encoding-Decoding Strategy under Bitrate Constraints - Cao, Zhipeng; Jia, Chaoqing; Hu, Jun; Luo, Ruonan (Proceedings (IEEE ... International Conference on Control Science and Systems Engineering. Online), 2023)
In this paper, the attack-resilient state estimation problem is investigated for uncertain complex networks (UCNs) with fading measurements and encoding-decoding scheme under bitrate constrains (EDSBC). First of all, the phenomenon of fading measurements is described by the attenuation coefficient matrix governed by uniform distributed random variables within a given interval. Subsequently, the false data injection attack (FDIA) is modeled by a bounded signal sequence and an encoding-decoding scheme subject to bitrate constrains is employed to schedule data through a bandwidth-limited channel. An EDSBC-dependent state estimation method against FDIA and fading measurements for UCNs is developed such that an upper bound of error covariance of state estimation is obtained and the state estimator gain is determined in the sense of mean-square error (MSE). Finally, the derived results are demonstrated by a numerical simulation with respect to effectiveness and feasibility.